(untitled) (Bangladesh Journal of Medical Science, 2016)
Non recurrent laryngeal nerve is a rare anatomical variation with an incidence in literature of 0.3 % to 1.6 % on the right side. This variation places the nerve at risk of inadvertent injury during head and neck surgeries. Awareness about this abnormality and meticulous dissection of the nerve in every case is the only way to stay safeguarded. Here we present a case of right non recurrent laryngeal nerve in a 32 years old female patient who underwent near total thyroidectomy for nontoxic multi nodular goitre. During surgery, the right recurrent laryngeal nerve could not be identified in its normal location. Further dissection revealed a non recurrent laryngeal nerve arising from the vagal trunk. A CT angiogram was done post operatively and showed an anomalous origin of the right subclavian artery as the last branch of the aortic arch and a bi-carotid trunk. Every surgeon operating on the neck should be aware of and anticipate this variation of the recurrent laryngeal nerve especially when the nerve cannot be identified in the normal location. Bangladesh Journal of Medical Science Vol.15(3) 2016 p.485-487